ANALISIS KATA φίλος DAN ἀγαπάω DALAM YOHANES 15:9-17 SEBAGAI UPAYA MERUMUSKAN TEOLOGI SAHABAT - Stenly Reinal Paparang (Manna Rafflesia, 2025)
Conversations about the meaning of friend have a variety of empirically and theoretically based definitions. In the text of John 15:9-17, Jesus presents the context of the identity of friends - φίλος, which is associated with the principle of mutual love - ἀγαπάω. This principle gives room for faith to realize love in pluralistic life. Being a “friend” is a new identity revealed by Jesus, contrasting with the identity of “servant”. The meaning of friend is different from what philosophers and those who have experienced it have expressed. Jesus placed the identity of a friend beyond what is commonly discussed. The new identity denies acts of hostility, hatred and violence. To achieve this goal, an exegetical approach is taken to the relevant texts, tracing various sources and presenting different interpretations, analyzing them to formulate their meaning. The meaning of the word “philos” is very diverse, and is associated with the attitude of “love”. Even in this context, the meaning also extends to the enemies as recommended by God, and based on God's mercy. This is then associated with Jesus who loves sinful man. He also gave a new identity of 'friend. The diversity of meanings of friend and love indicates that in formulating the theology of friends, it creates a dynamic hermeneutical principle. In this effort, the research presents a novelty in the formulation of the theology of companions that emphasizes three things: First, the context of the incarnation connected to redemption as a form of God's love for believers (vv. 9-13). Second, the context of Jesus' election of His people (v. 16). Third, the context of the coherence of love for God that is manifested in the relationship with others (vv. 12, 17). In addition, this study contributes to the attitude of loving one another so that it has a positive impact on pluralistic life, living in peace, love, and competing with each other in doing good.